Antibacterial activities against Porphyromonas gingivalis and biological characteristics of copper-bearing PEO coatings on magnesium. (20th January 2021) - Zhang, Dan; Han, Qi; Yu, Kun; Lu, Xiaopeng; Liu, Ying; Lu, Ze; Wang, Qiang
Abstract: Unlike other parts of the body, jaw defection often involves dental and periodontal tissues, which colonized a great many oral anaerobic bacteria. As a remarkable degradable material, magnesium has become an excellent candidate for orthopedic appliances recently. But the high degradation rate is still a big problem. Making a biodegradable coating with good biocompatibility to slow down the degeneration rate of magnesium is one of the best methods. However, protective coatings will impair the antibacterial effects of magnesium which is caused by the rise of pH value throughout its degradation. To solve this problem, a series of composite coatings with different amounts of CuO particles (3, 5 and 7 wt.%) were fabricated on pure magnesium through plasma electrolytic oxidation (PEO) to investigate in vitro biocompatibility and the antibacterial abilities against Porphyromonas gingivalis ( P. gingivalis ). Surface characterization and degradation behavior of the copper-bearing PEO coatings were also systematically studied. Furthermore, the most optimum coating was also systematically studied by X-ray photoelectron spectroscopy (XPS) and electrochemical corrosion test. Results of the present research revealed that adding proper amount of CuO into PEO coatings could greatly improve the antibacterial abilities of the PEO coatings. The antibacterial activities of copper-bearing PEO coatings were excellent and revealed concentration-dependent and time-dependent. Biocompatibility of copper-bearing PEO coatings showed that proper amount of Cu could promote cell proliferation. Compared with other PEO coatings in this study, PEO-7Cu showed some inhibition effects on cell proliferation and adhesion for long-term use. Electrochemical corrosion tests and immersion tests showed that PEO-5Cu and PEO-7Cu copper-bearing PEO coatings would provide satisfying corrosion resistance effects, while PEO-3Cu was poorer than PEO coatings without Cu. However, compared with uncoated pure magnesium, the corrosion resistance of the PEO coating was much better. Based on the results of antibacterial ability, biocompatibility, and corrosion resistance of the above copper-bearing PEO coatings, PEO-5Cu in this research was recommended to be used in patients with jaw defects.